1983
DOI: 10.1007/bf02405022
|View full text |Cite
|
Sign up to set email alerts
|

Errors in measuring trabecular bone by computed tomography due to marrow and bone composition

Abstract: The linear attenuation coefficient (mu in cm-1) of trabecular bone was modeled for different conditions of bone and marrow composition in order to assess their influence on computed tomography (CT) quantitation. A large relative change (10% of TBV at 15% TBV) of bone concentration resulted in small changes of mu: 2.3% at 60 keV, 3.4% at 44 keV, 5.2% at 29 keV. Relative changes of trabecular bone volume (TBV) on the order of 3% could be detected in vivo by CT were it not for errors of relocation and for composi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
44
0
1

Year Published

1984
1984
2002
2002

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 104 publications
(45 citation statements)
references
References 29 publications
0
44
0
1
Order By: Relevance
“…It is possible to reduce this 5-fold (66,69). A high kilovoltage also is undesirable because it increases the large accuracy errors (at least 15-25%) associated with variable marrow fat and varying osteoid (83)(84)(85)(86)(87)(88)(89)(90)(91)(92)(93)(94)(95)(96)(97)(98). Gluer et al (99) showed an error of ash density of 8 mg/cm3 for every 100 mg/cm3 change of marrow fat, but the error at higher energies is 10-13 mg/cm3, i.e., 30-50% greater (85,92,(99)(100)(101).…”
Section: Measurement Methodsmentioning
confidence: 99%
“…It is possible to reduce this 5-fold (66,69). A high kilovoltage also is undesirable because it increases the large accuracy errors (at least 15-25%) associated with variable marrow fat and varying osteoid (83)(84)(85)(86)(87)(88)(89)(90)(91)(92)(93)(94)(95)(96)(97)(98). Gluer et al (99) showed an error of ash density of 8 mg/cm3 for every 100 mg/cm3 change of marrow fat, but the error at higher energies is 10-13 mg/cm3, i.e., 30-50% greater (85,92,(99)(100)(101).…”
Section: Measurement Methodsmentioning
confidence: 99%
“…Reich et al (1976) were also using the CT single-energy tech-nique, and their report is in agreement with our findings. As earlier stated (Mazess 1983) dual-energy computed tomography increases the accuracy, but the precision may be reduced compared with single-energy computed tomography. Mechanical tests have shown that rotational and axial loading of the femur have the highest correlation with the QCT bone-massrelated measurements (Alho et al 1988, Husby et al 1989).…”
Section: Discussionmentioning
confidence: 86%
“…Earlier reports have mainly dealt with CT measurements of mean density within a defined volume of bone, thus including both cortical bone and bone marrow (Mazess 1983, Bentzen et al 1987. Our approach, by defining a lower density threshold limit, may, to some extent, reduce this error.…”
Section: Discussionmentioning
confidence: 99%